Implikasi Pernikahan Usia Remaja Terhadap Pola Asuh Anak dalam Keluarga - Muru’atul Afifah; Amina Amina (Medan Resource Center, 2023)
Early marriage remains prevalent in village communities deeply rooted in culture and customs, leading to various social problems. This study aims to describe the implications of early marriage on child care in Larangan Perreng Village, focusing on factors causing early marriage, forms of child care, and the resulting implications. Qualitative field research was conducted in Larangan Perreng Village to gather data, and triangulation techniques were employed to ensure data validity. Economic, self, and parental factors were identified as contributors to early marriage in the village. Couples who married early adopted democratic, permissive, and authoritarian parenting styles to raise their children. The findings revealed that early marriage had negative implications on parenting, including increased household conflicts, adverse effects of physical punishment on children's well-being, suboptimal parenting practices, and insufficient independence in child-rearing. These outcomes highlight the importance of addressing early marriage and promoting effective child care strategies within the community.